(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This research paper provides a comprehensible review of the essential factors in English Language Teaching in face-to-face class. The study identifies specific characteristics of Technology-enhanced language learning, interaction, motivation, usage of real communicative activities in teaching English as a foreign language. After investigating research papers on the important aspects of teaching English, suggestions and recommendations are proposed to use in conducting EFL effectively in traditional classrooms.